DAMPAK PANDEMI COVID-19 TERHADAP PHK DAN PENDAPATAN PEKERJA DI INDONESIA - Ngadi Ngadi; Ruth Meliana; Yanti Astrelina Purba (Research Centre for Population, Indonesian Institute of Sciences, 2020)
The larger-scale social restrictions policy to handling the COVID-19 pandemic had an impact on the socio-economic of the community including job sustainability and income of workers. This study analyzes the impact of the COVID-19 on worker layoffs and income in Indonesia. This research uses an accidental sampling through the online survey. The results showed that COVID-19 had an impact on layoffs and decreased income, especially during the social distancing. The result showed that layoffs of workers in Indonesia amounted to 15.6 percent.Â Regarding income, about 31.0 percent of workers claim that their income has decreased by less than 50 percent and 8.6 percent of that has fallen above 50 percent. The government needs to conduct strict supervision of companies in each region. The role of the community is needed in overcoming existing problems by looking for new strategies that are utilizing technology and looking for new job opportunities, while still paying attention to health protocols.